2021
DOI: 10.3390/rs13030392
|View full text |Cite
|
Sign up to set email alerts
|

Crop Height Estimation of Corn from Multi-Year RADARSAT-2 Polarimetric Observables Using Machine Learning

Abstract: This study presents a demonstration of the applicability of machine learning techniques for the retrieval of crop height in corn fields using space-borne PolSAR (Polarimetric Synthetic Aperture Radar) data. Multi-year RADARSAT-2 C-band data acquired over agricultural areas in Canada, covering the whole corn growing period, are exploited. Two popular machine learning regression methods, i.e., Random Forest Regression (RFR) and Support Vector Regression (SVR) are adopted and evaluated. A set of 27 representative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 78 publications
(116 reference statements)
3
17
0
Order By: Relevance
“…The crop structural features were also well characterized by their unique scattering patterns using parameters derived from polarimetric decompositions (i.e., FD, CP, and ND). The difference in temporal evolution patterns of scattering mechanisms among crops provided useful information for crop classification, which have been frequently used in crop growth monitoring and classification in previous reports [7,17,27,38,39,41]. Among the polarimetric complex correlation parameters, the correlation coefficient ρ HHVV showed the highest sensitivity to crop growth, which has been proven useful for identification of growth stages [31,36].…”
Section: Temporal Evolutions Of Polarimetric Observablesmentioning
confidence: 96%
See 2 more Smart Citations
“…The crop structural features were also well characterized by their unique scattering patterns using parameters derived from polarimetric decompositions (i.e., FD, CP, and ND). The difference in temporal evolution patterns of scattering mechanisms among crops provided useful information for crop classification, which have been frequently used in crop growth monitoring and classification in previous reports [7,17,27,38,39,41]. Among the polarimetric complex correlation parameters, the correlation coefficient ρ HHVV showed the highest sensitivity to crop growth, which has been proven useful for identification of growth stages [31,36].…”
Section: Temporal Evolutions Of Polarimetric Observablesmentioning
confidence: 96%
“…The results using single groups of polarimetric observables showed that polarimetric decompositions (ND, FD, and CP), backscattering coefficients in Pauli and linear polarimetric channels, and correlation coefficients produced the best classification accuracies, with OAs greater than 87%. This is because these polarimetric observables were found to be very sensitive to crop structure and growth parameters [7,17,27,38,39,41]. In previous studies, the common way for constructing the feature set was by stacking all polarimetric observables from various sources [7,17,27,39].…”
Section: Crop Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaf chlorophyll content directly influences the amount of light captured during photosynthesis and, thus, the amount of energy available for yield production. Remote sensing can also directly measure height [22][23][24], which can be related to crop biomass allometrically and thereby to yield. Taking advantage of new high-resolution satellite data and drone-mounted sensors, it is now possible to produce maps of these yield-related parameters at sub-field scale with known accuracy [25].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, research on L-band co-polarized phase differences on crops is scarce (e.g., [20]). Most of the research using polarimetric SAR data relied on higher frequencies (C-and X-band) [21][22][23] or multi-polarization intensity-only studies [24]. These shortcomings will be addressed in this manuscript, which turns out to be a novel contribution of this work.…”
Section: Introductionmentioning
confidence: 99%